The impact of bullying cognition on school bullying among Chinese primary school students: a moderated mediation model of resilience and sex - Fei, Liping; Li, Tianwen; Li, Yongli; Liao, Maoxu; Li, Xin; Chen, Yiting; Zhang, Rong (Frontiers in Public Health, 2024)
Background: Previous studies have shown the positive effects of bullying cognition on school bullying behavior among young people, but the mechanism underlying this association remains unclear.We conducted a cross-sectional study with 5,903 primary school students in grades 3-5 in Luzhou city. Hayes' PROCESS macro was used to test the mediating effect of psychological resilience and the moderating effect of sex on the relationship between bullying cognition and school bullying after controlling for grade.Results: Psychological resilience partially mediated the relationship between school bullying cognition and victimization (β = -0.0174, 95% CI: -0.0219 to -0.0132) and between perpetration (β = -0.0079, 95% CI: -0.0104 to -0.0055). This study revealed that sex moderated the relationship between school bullying cognition and perpetration (β = 0.0383, p < 0.001) and victimization behavior (β = 0.0400, p < 0.001).These findings suggest that it is crucial for education regulators, schools, and families to cultivate students' school bullying cognitions and psychological resilience, which may help to decrease the prevalence of school bullying. Especially for boys, improving their bullying cognition may largely decrease its perpetration.